2014
DOI: 10.1002/pits.21808
|View full text |Cite
|
Sign up to set email alerts
|

Assessment, Prevention, and Intervention for Abuse Among Individuals With Disabilities

Abstract: Individuals with disabilities are at increased risk for abuse by their parents, caretakers, and the staff who are entrusted with their care as well as from the general population. Many individuals with disabilities have cognitive or communication impairments that place them at even higher risk for abuse. These limitations also make it more difficult for school psychologists and other clinicians to assess abuse history. Further, full participation in traditional prevention or treatment programs may not be feasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 46 publications
(61 reference statements)
0
11
0
2
Order By: Relevance
“…In the literature, it was reported that individuals with DD have difficulties in safety related skills such as realizing and describing a dangerous condition, presenting appropriate behavior in an appropriate time when they face a dangerous condition, protecting one self and maintaining his/her own safety, reporting a negative condition or crime to parents or other adults around him/her and asking for help (Kenny, Bennett, Dougrey and Steele, 2013;Mechling, 2008). Due to these reasons, teaching safety skills systematically to individuals with any kinds of disabilities has vital importance (Agran, Krump, Spooner and Traice-Lynn, 2012;Kıyak, Tuna and Tekin-İftar, 2019;Mechling, 2008;Sirin and Tekin-Iftar, 2016;Wilczynski, Connolly, Dubard, Henderson and Mcintosh, 2015).…”
Section: Importance Of Teaching Safety Skills To Individuals With Devmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, it was reported that individuals with DD have difficulties in safety related skills such as realizing and describing a dangerous condition, presenting appropriate behavior in an appropriate time when they face a dangerous condition, protecting one self and maintaining his/her own safety, reporting a negative condition or crime to parents or other adults around him/her and asking for help (Kenny, Bennett, Dougrey and Steele, 2013;Mechling, 2008). Due to these reasons, teaching safety skills systematically to individuals with any kinds of disabilities has vital importance (Agran, Krump, Spooner and Traice-Lynn, 2012;Kıyak, Tuna and Tekin-İftar, 2019;Mechling, 2008;Sirin and Tekin-Iftar, 2016;Wilczynski, Connolly, Dubard, Henderson and Mcintosh, 2015).…”
Section: Importance Of Teaching Safety Skills To Individuals With Devmentioning
confidence: 99%
“…). Bu nedenle, güvenlik becerilerinin hangi yetersizlik kategorisinde olursa olsun tüm özel gereksinimli bireylere sistematik biçimde öğretilmesi yaşamsal önem taşımaktadır (Agran, Krump, Spooner ve Traice-Lynn, 2012;Ergenekon, 2012;Kıyak, Tuna ve Tekin-İftar, 2019;Mechling, 2008; Şirin ve Tekin-İftar, 2016;Wilczynski, Connolly, Dubard, Henderson ve Mcintosh, 2015).…”
unclassified
“…Indeed, different studies suggest that between 39% and 60% of women with ID are at risk of being sexually abused compared with 16% to 30% of men with ID (Swango-Wilson, 2009). Thus, women with ID are considered more vulnerable to SA than men, even when other risk factors are present to a similar degree (Gil-Llario et al, 2018; Liou, 2014; Wilczynski, Connolly, Dubard, Henderson, & Mcintosh, 2011). As to the degree of disability, several studies showed higher vulnerability to SA in people with moderate or mild ID, compared with individuals with severe ID (Balogh et al, 2001; Liou, 2014; Morell-Mengual, Gil-Llario, Díaz-Rodríguez, Castro-Calvo, & Ceccato, 2016; Pan, 2007; Zirpoli et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Professionals play a significant role with regard to the care surrounding (alleged) sexual abuse. They have an important task in recognizing physical, behavioral and emotional signs of abuse in people with ID [ 9 , 10 ] and to determine a subsequent course of action. However, the support provided by professionals is expected to be optimal only when they are sufficiently informed about the characteristics and care demands of people with ID and aware of available assessment and treatment possibilities regarding sexual abuse.…”
Section: Introductionmentioning
confidence: 99%
“…However, to the best of our knowledge no studies have evaluated such training courses for psychologists, specifically aimed at the assessment of sexual abuse. Assessment of sexual abuse is important in order to: clarify the event(s) of sexual abuse and its consequences, clarify the developmental history to explain the behavior and estimate the risk of reoccurrence [ 15 , 16 ], and support individuals with ID to disclose the abuse in a nonthreatening way [ 9 ]. Despite the importance of assessment of sexual abuse, research shows that most psychologists received only limited training in the area of sexuality and that these gaps in knowledge and skills are not being filled through continuing education [ 17 ].…”
Section: Introductionmentioning
confidence: 99%